Nightspell - Cypess, Leah (Greenwillow Books, 2011)
Sent by her father, the king of Raellia, who is trying to forge an empire out of warring tribes, Darri arrives in Ghostland and discovers that her sister, whom she planned to rescue, may not want to leave this land where the dead mingle freely with the living.